The Use of Estafet Writing Method in Learning Short Story Writing of Grade XI Students of Vocational School - Aisyah, AzimatulMillah; Rokhmansyah, Alfian (Jurnal Ilmu Manajemen dan Pendidikan, 2024)
This study aims to implement the estafet writing method to improve the short story writing skills of Grade XI students at SMK Kesehatan Madani Indonesia. The study employed a Classroom Action Research method conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. Data collection techniques were carried out through direct observation and interviews with teachers and students. The results showed that the implementation of the estafet writing method effectively improved students' short story writing skills. In the first cycle, student participation increased, although challenges remained in discussions and story structuring. In the second cycle, with smaller group formations and more focused themes, students demonstrated significant improvements in contribution, creativity, and the quality of their writing. The average student scores increased from the pre-cycle to the second cycle, with a completion rate reaching 100%. This method not only enhanced students' writing skills but also fostered teamwork, creativity, and active participation in learning.